1D p–n Junction Electronic and Optoelectronic Devices from Transition Metal Dichalcogenide Lateral Heterostructures Grown by One-Pot Chemical Vapor Deposition Synthesis - Najafidehaghani, Emad; Gan, Ziyang; George, Antony; Lehnert, Tibor; Ngo, Gia Quyet; Neumann, Christof; Bucher, Tobias; Staude, Isabelle; Kaiser, David; Vogl, Tobias; Huebner, Uwe; Kaiser, Ute; et al. (Advanced Functional Materials, 2021)
Lateral heterostructures of dissimilar monolayer transition metal dichalcogenides provide great opportunities to build 1D in-plane p–n junctions for sub-nanometer thin low-power electronic, optoelectronic, optical, and sensing devices. Electronic and optoelectronic applications of such p–n junction devices fabricated using a scalable one-pot chemical vapor deposition process yielding MoSe2-WSe2 lateral heterostructures are reported here. The growth of the monolayer lateral heterostructures is achieved by in situ controlling the partial pressures of the oxide precursors by a two-step heating protocol. The grown lateral heterostructures are characterized structurally and optically using optical microscopy, Raman spectroscopy/microscopy, and photoluminescence spectroscopy/microscopy. High-resolution transmission electron microscopy further confirms the high-quality 1D boundary between MoSe2 and WSe2 in the lateral heterostructure. p–n junction devices are fabricated from these lateral heterostructures and their applicability as rectifiers, solar cells, self-powered photovoltaic photodetectors, ambipolar transistors, and electroluminescent light emitters are demonstrated.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D devices; lateral heterostructures; light-emitting diode; p–n junction; transition metal dichalcogenides monolayers